2003
DOI: 10.1002/marc.200350030
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Biomineralization: Mirror‐Imaged Helical Growth of Calcite with Chiral Phosphoserine Copolypeptides

Abstract: The O‐phospho‐L‐serine [Ser(P)] containing peptides and proteins play an important role in controlling the morphology of biominerals. The poly[Ser(P)] and copoly[Ser(P)xAspy] affect the calcium carbonate (CaCO3) morphology and polymorph. The CaCO3 helical structures were obtained in the presence of copoly[Ser(P)75Asp25]. When the L‐copolymer was used as an additive, a clockwise P twisted spiral morphology was formed. On the other hand, when using D‐copolymer, a counterclockwise M twisted spiral morphology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 13 publications
(13 reference statements)
2
65
0
2
Order By: Relevance
“…Asp), [2] and the random copolypeptides, poly[Ser(PO 3 H 2 ) Xco-Asp Y ] (X: Y ¼ 75: 25, 50:50, 25:75). [3] More recently, we applied our method to the synthesis of the Thr(PO 3 H 2 )-containing random and sequential polypeptides. [4] These synthetic phosphorylated polypeptides were used in a series of experiments on calcium carbonate crystallization, and several kinds of characteristic crystal morphologies were observed in the presence of the Ser(PO 3 H 2 )-containing and Thr(PO 3 H 2 )-containing polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Asp), [2] and the random copolypeptides, poly[Ser(PO 3 H 2 ) Xco-Asp Y ] (X: Y ¼ 75: 25, 50:50, 25:75). [3] More recently, we applied our method to the synthesis of the Thr(PO 3 H 2 )-containing random and sequential polypeptides. [4] These synthetic phosphorylated polypeptides were used in a series of experiments on calcium carbonate crystallization, and several kinds of characteristic crystal morphologies were observed in the presence of the Ser(PO 3 H 2 )-containing and Thr(PO 3 H 2 )-containing polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The combinations of protecting and deprotecting methods for phosphoryl groups on Thr and Ser residues were more advanced in these periods, and successful syntheses were described for a calcium phosphate-binding peptide with multiple Thr(PO 3 Ph 2 ) residues, [16] Thr(PO 3 H 2 )-containing peptides of the EGF receptor protein sequence, [18] the Thr(PO 3 H 2 )-and Ser(PO 3 H 2 )-coexisting rhodopsin C-terminal peptide, [19] and so on. The methodology for introducing protected-phosphoryl groups into the peptides, together with the combinations of removal of the protecting groups, were further extended by the development of various protection and deprotection methods, many of which have been reported by Wakamiya et al [20][21][22] and by Otaka et al [23][24][25] More recently, we reported the extension of the phenylprotecting strategy to the synthesis of random and sequential polypeptides containing Ser(PO 3 H 2 ), for instance, poly [Ser(PO 3 H 2 )], [26] copoly[Ser(PO 3 H 2 ) X Asp Y ] (X:Y ¼25:75, 50:50, 75:25), [27] poly[Ser(PO 3 H 2 )-Xaa] (Xaa ¼ Gly, Ala, Ser, Asp, Glu, or Lys), and poly[Gly-Ser(PO 3 H 2 )-Gly]. [28] The copolypeptides copoly[Ser(PO 3 H 2 ) X Asp Y ] were revealed as useful models of the substrate proteins of biominerals, capable of varying the polymorphs and crystal shapes of CaCO 3 , dependent on the stoichiometry between the Ser(PO 3 H 2 ) residues and the Ca 2þ ions.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] We also previously described the experimental conditions for the CaCO 3 crystallization and developed a hypothesis for the growth mechanism of the characteristic fibrous calcite crystals and the helical calcite based on WXRD, SEM-EDX and selected-area electron diffraction (SAED) analyses.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13] The synthetic copolypeptides composed of aspartic acid (Asp) and Ser(PO 3 H 2 ) residues induced several kinds of calcium carbonate crystal morphologies, for example, fibrous and helical calcites and spherical vaterite crystals. [13] These results clearly indicated that the Ser(PO 3 H 2 )-containing polypeptides are an effective crystal growth modifier for the calcium biominerals.…”
Section: Introductionmentioning
confidence: 99%